Fusarium oxysporum e Aspergillus sp. como produtores de queratinases utilizando resíduos agroindustriais - Preczeski, Karina Paula (2020)
Keratinases act in the hydrolysis of keratin, a complex component present in some agro-industrial residues, such as swine hair and chicken feathers. The treatment of these residues is important for their recovery and to avoid environmental pollution. Technological processes mediated by fungi and enzymes are promising alternatives for the treatment of recalcitrant residues. Considering this, the present study evaluated strategies for obtaining keratinases produced by fungi using submerged fermentation (SF) and solid-state fermentation (SSF). Two fungi isolated from feather residues showed potential for the production of keratinases, Fusarium oxysporum and Aspergillus sp. These strains were used in the FS together with feathers or swine hair prepared in three different conditions (microbial concentration reduction, sterilization and treatment with hydrogen peroxide). The residual fermented mass was quantified and tested for new enzymatic production. The fungus with the greatest capacity to produce keratinases in SF was used to produce keratinases in SSF, using grape residues and/or swine hair as a substrate. The most promising enzymatic extract of each fermentation was carried out using the enzymatic precipitation technique using salts and organic solvents. The greatest keratinolytic activity in the SF was obtained with F. oxysporum (243.50 U mL-1) after six days of fermentation, using sterile swine hair. In SSF, the highest keratinolytic activity was obtained in nine days (518.66 U g-1), using only hair residues as a substrate. In the enzymatic precipitation, a purification factor of 127.13 times in the FS and 14.08 times in the FES was obtained, both in the supernatant phase, with enzymatic yields above 100%. In the reuse of swine hair, the keratinase activity remained at 74.74% of the initial activity after 3 cycles, presenting potential for enzymatic production for application in various environmental problems. The use of residues for the production of keratinolytic enzymes proved to be a promising strategy for application in the biotechnological area, obtaining enzymes with high activity after simple processes of enzymatic concentration, in addition to the residue being susceptible to fermentative recycling without significant production losses.